Multi-fractality in aeroelastic response as a precursor to flutter. (6th January 2017) - Venkatramani, J.; Nair, Vineeth; Sujith, R.I.; Gupta, Sayan; Sarkar, Sunetra
Abstract: Wind tunnel tests on a NACA 0012 airfoil have been carried out to study the transition in aeroelastic response from an initial state characterised by low-amplitude aperiodic fluctuations to aeroelastic flutter when the system exhibits limit cycle oscillations. An analysis of the aeroelastic measurements reveals multi-fractal characteristics in the pre-flutter regime. This has not been studied in the literature. As the flow velocity approaches the flutter velocity from below, a gradual loss in multi-fractality is observed. Measures based on the generalised Hurst exponents are developed and are shown to have the potential to warn against impending aeroelastic flutter. The results of this study could be useful for health monitoring of aeroelastic structures. Abstract : Highlights: Multifractality observed in the aeroelastic response in wind tunnel experimental. Multifractality is non-existent in post-flutter response. Multifractal behaviour of aeroelastic response has not been reported in the literature. Hurst exponents calculated from aeroelastic response behave as precursors to flutter.